gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Characterization of rice husk ash glass produced at low temperature as a sustainable alternative for the glass industry - J. M. M. Marçal; M. R. Chim; I. M. Teixeira; L. E. G. Armas; S. Buchner; M. Vasconcellos; J. W. Menezes; C. Valsecchi (International Journal of Environmental Science and Technology, 2025)

Strengthening Amazon conservation through community‐based voluntary patrolling - Caetano L. B. Franco; Thais Q. Morcatty; Helder L. Queiroz; Michael G. Sorice; Julia E. Fa; Paulo Roberto e Souza; Isabel S. Sousa; João Valsecchi; Hani R. El Bizri (Conservation Biology, 2025)
Globally, environmental crimes are a major threat to biodiversity and the livelihood of local populations. Community‐based protection of natural resources, which involves local people in surveillance and enforcement, is an important complement to the government‐led command‐and‐control policing approach. We examined whether a community‐based voluntary patrolling system deterred environmental crimes in Amazonia. We used data on environmental crimes recorded by patrollers over 11 years (2003–2013) in 12 independent territorial units in 2 large protected areas (PAs) in Amazonas, Brazil. For comparison, we also analyzed data from government‐led enforcement operations outside these PAs from 2002 to 2012. In total, patrollers conducted almost 20,000 surveillance outings (around 150,000 h of activity) and recorded the occurrence of 1260 crimes. Of the 772 crimes for which we had data on seized items, most violations were related to fishing (78.24%), 19.04% to hunting, or 2.72% to logging. The occurrence of crimes per outing increased as the number of patrollers and time spent patrolling increased and was greater during outings that were informant led. There was a sharp decrease over time in the occurrence of crimes during patrols across 11 of the 12 territorial units examined. Overall, the occurrence of crimes declined by approximately 80% over the study period. In contrast, the number of crimes detected over time during government‐led enforcement operations outside the PAs did not decline. Leadership of local communities in the planning and conducting of patrols contributed to rule conformity and enforcement in the PAs. Our results should be especially useful to managers of PAs and researchers in other parts of the tropics as a model for local patrolling and natural resource protection.

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Urban wild meat consumption and trade in central Amazonia - Hani R. El Bizri; Thaís Q. Morcatty; João Valsecchi; Pedro Mayor; Jéssica E. S. Ribeiro; Carlos F. A. Vasconcelos Neto; Jéssica S. Oliveira; Keilla M. Furtado; Urânia C. Ferreira; Carlos F. S. Miranda; Ciclene H. Silva; Valdinei L. Lopes; et al. (Conservation Biology, 2020)
The switch from hunting wild meat for home consumption to supplying more lucrative city markets in Amazonia can adversely affect some game species. Despite this, information on the amounts of wild meat eaten in Amazonian cities is still limited. We estimated wild meat consumption rates in 5 cities in the State of Amazonas in Brazil through 1046 door‐to‐door household interviews conducted from 2004 to 2012. With these data, we modeled the relationship between wild meat use and a selection of socioeconomic indices. We then scaled up our model to determine the amounts of wild meat likely to be consumed annually in the 62 urban centers in central Amazonia. A total of 80.3% of all interviewees reported consuming wild meat during an average of 29.3 (CI 11.6) days per year. Most wild meat was reported as bought in local markets (80.1%) or hunted by a family member (14.9%). Twenty‐one taxa were cited as consumed, mostly mammals (71.6%), followed by reptiles (23.2%) and then birds (5.2%). The declared frequency of wild meat consumption was positively correlated with the proportion of rural population as well as with the per capita gross domestic product of the municipality (administrative divisions) where the cities were seated. We estimated that as much as 10,691 t of wild meat might be consumed annually in the 62 urban centers within central Amazonia, the equivalent of 6.49 kg per person per year. In monetary terms, this amounts to US$21.72 per person per year or US$35.1 million overall, the latter figure is comparable to fish and timber production in the region. Given this magnitude of wild meat trade in central Amazonia, it is fundamental to integrate this activity into the formal economy and actively develop policies that allow the trade of more resilient taxa and restrict trade in species sensitive to hunting.

Direct measurement of nutrient concentrations in freshwaters with a miniaturized analytical probe: evaluation and validation - D. Copetti; L. Valsecchi; A. G. Capodaglio; G. Tartari (Environmental Monitoring and Assessment, 2017)